Factor IX Alloantibodies Shorten the Bovine Thromboplastin Coagulation Time of Normal Human Plasma - Ørstavik, Karen Helene (Thrombosis and Haemostasis, 1981)
We have previously demonstrated that neutralization of factor IX in normal plasma by heterologous antisera shortens the one stage prothrombin time determined with bovine thromboplastin. In this study, a similar effect of homologous antibodies was demonstrated. Addition of plasma from two patients with hemophilia B- and an acquired inhibitor to factor IX gave a shortening of the prothrombin time of plasma from normal persons, compared to the prothrombin time determined after addition of control plasma from a patient with hemophilia B- and no inhibitor. Addition of inhibitor plasma had a similar effect on the prothrombin time of plasma from four patients with hemophilia B+ and one patient with hemophilia Br, but had no effect on the prothrombin time of plasma from ten patients with hemophilia B-. Complexes between factor IX and the human inhibitor could be demonstrated both before and after the coagulation with bovine thromboplastin. These complexes were demonstrated as a factor IX antigen with a reduced electrophoretic mobility in crossed immunoelectrophoresis against a rabbit antiserum to factor IX. The results demonstrate that normal factor IX loses the ability to act as an inhibitor in the coagulation with bovine thromboplastin after having formed a soluble complex with a homologous antibody, although the factor IX molecules still have antigenic determinants which are free to react with the rabbit antibodies.
Keywords: Factor IX; Bovine thromboplastin; Alloantibodies